Gene Editing and Alzheimer's Disease: Is There Light at the End of the Tunnel? - Stepanichev, Mikhail (Frontiers in Genome Editing, 2020)
Alzheimer's disease continues to be a fatal, incurable neurodegenerative disease, despite many years of efforts to find approaches to its treatment. Here we review recent studies on Alzheimer's disease as a target for gene therapy and specifically, gene editing technology. We also review the opportunities and limitations of modern methods of gene therapy based on the CRISPR editing system. The opportunities of using this approach for modeling, including cellular and animal models, studying on pathogenesis and disease correction mechanisms, as well as limitations for its therapeutic use are discussed.